The Influence of Moisture on the Frequency Spectrum of Time Varying Mass Engineering Structure - Phung Tu; Vanissorn Vimonsatit; Chayanon Hansapinyo (Salehan Institute of Higher Education, 2023)
The frequencies of time-varying mass systems have not been commonly studied in engineering structures as the rate of mass change is generally small compared to the mass of the overall structure. For silos of granular materials, the total mass of the stored granules can be relatively high compared to the mass of the silo structure. During the flow-in or flow-out of granules, the silo system behaves as a time-varying mass system. Minor changes to the moisture content ratio of the granules can cause their flow characteristics to change. The influence of the moisture content ratio of the granular material inside a cylindrical silo is investigated in this paper using Variational Mode Decomposition, Hilbert Transform, and Hilbert Marginal Spectrum processing methods. The results show that the amplitude and frequency of vibration vary with the change in the moisture content ratio of the stored materials and across different cycles, despite all influencing parameters being kept constant. Such variations in the response of the structure mean that the loads also vary according to the principles of engineering mechanics. The outcomes of this research can be further developed into a diagnostic tool to conditionally monitor the structural integrity of the overall silo structure and flow characteristics automatically. Doi: 10.28991/CEJ-2023-09-01-02 Full Text: PDF